Testing Rigidity Transitions in Glass and Crystal Forming Dense Liquids: Viscoelasticity and Dynamical Gaps - Toledo-Marín, J. Quetzalcóatl; Naumis, Gerardo G. (Frontiers in Materials, 2019)
A computational study of rigidity for dense fluids of monodisperse and bidisperse hard-disks near a phase and a glass transition respectively is presented. To achieve this goal, the transversal part of the dynamical structure factor is calculated. In both cases, a viscoelastic behavior is obtained, with a dynamical gap determined by a critical wavevector $k_c$. Transversal waves exist for $k>k_c$ while density-density correlations happens at frequency $ω=0$ for $k<k_c$. In both cases $k_c$ goes to zero as the freezing point is approached. Both systems are able to fulfill a scaled dynamical law. The obtained results indicate that this method gives an alternative to study rigidity in dense fluids, since it is possible to assign a number of floppy modes to the liquid. Also, this suggests that the critical wavevector $k_c$ can serve as a suitable order parameter.